Development of pyrazolo[3, 4-d]pyrimidin-4-one scaffold as novel CDK2 inhibitors: Design, synthesis, and biological evaluation. (15th August 2022) - Xie, Fan; Zhou, Liying; Ge, Changwei; Song, Xiuqing; Yan, Hong
Graphical abstract: Abstract: A series of pyrazolo[3, 4- d ]pyrimidin-4-one scaffold were designed and synthesized as novel CDK2 inhibitors. By analyzing the common motifs of various known inhibitors, the designed compounds 1 were virtually screen for their inhibitory activity by docking into the active pocket of CDK2. The influence of different substitutes on the docking results was investigated. A total of 15 pyrazolo[3, 4- d ]pyrimidin-4-ones 1 were synthesized by Paal-Knorr reaction, pyrimidine ring closure, bromination, Suzuki coupling reaction, amide formation and Knoevenagel condensation. The Cell Counting Kit-8 (CCK-8) was used to evaluate the inhibitory activity of pyrazolo[3, 4- d ]pyrimidin-4-ones 1 in the breast cancer cell line MCF-7 in vitro using Etoposide as a reference control substance. The screening results demonstrated that the designed compounds have significant antiproliferative activity, and compounds 1e and 1j were the most active compounds with IC50 values of 10.79 μM and 10.88 μM, respectively, being better than that of Etoposide (IC50  = 18.75 μM). The enzyme inhibition assay was carried out against CDK2, the results indicated that the compounds 1e and 1j significantly inhibited CDK2 with IC50 values of 1.71 μM and 1.60 μM.